Effects of different air drying temperature on sunflower seeds oil and ash content - Matin Ana; Krička Tajana; Jurišić Vanja; Voća Neven; Žunić Julijana; Grubor Mateja (Journal on Processing and Energy in Agriculture, 2017)
The aim of this paper was to determine the impact of different air temperature (60°C, 80°C and 100°C) at air drying velocity of 1.0 ms-1 during convection drying thermal process on the sunflower seeds oil and ash content. The research was conducted at 4 different sunflower seeds hybrid Apollo, NK Brio, PR 63 and PR 90 A 63 D 82, which by their characteristics are early and medium early hybrids. Based on the results, the curve of water speed release from the sunflower seeds, the activation energy, as well as changes in oil content and ash content before and after the convective drying was obtained. It was established that the NK Brio hybrid fastest release water compared to other hybrids during drying which is confirmed by minimum value of activation energy and that the increasing of air drying temperature increases oil content, while reduces ash content.